Proceedings of the Fifth International Coral Reef Congress, Tahiti, 27 May-1 June 1985. (Tahiti, French Polynesia Antenne Museum-Ephe, French Polynesia, 1985)
Contents : v.1 French Polynesian coral reefs; v.2 Abstracts : intended contributions; v.3 Symposia and seminars A; v.4 Symposia and seminars B; v.5 Miscellaneous papers A; v. 6 Miscellaneous papers B
Keywords: Coral reef; Coral reef biology